Rural income diversification in Rwanda: Opportunities and challenges - Schmidt, Emily; Mugabo, Serge; Rosenbach, Gracie (International Food Policy Research Institute, 2024)
The Government of Rwanda continues to work to accelerate structural transformation to expand and diversify the country’s economy. High rural population density and small agricultural landholdings are driving workers from agricultural households to seek employment outside of farming. Using representative data on agricultural production and employment for rural households in Rwanda from 2022, this research evaluates the opportunities rural households have to diversify their labor portfolios. We find that, rather than nonfarm household enterprises developing to meet greater rural service and goods demand, agriculture wage labor is the dominant source of off-own-farm employment. However, such informal agricultural wage labor is seen as low-productivity work and is among the lowest paid. Among nonfarm employment options, nonfarm businesses generate less income than nonagricultural wage labor, likely reflecting high barriers to entrepreneurship and low demand for off-farm services in rural areas.